The influence of social capital on service quality evaluation - Imrie, Brian C. * (Emerald Group Publishing Limited, 2013)
Purpose: This research provides guidance for the global manager by determining the manner through which social interaction influences service quality evaluation. Furthermore, this paper explores the function of economic development in altering the role of social relationships in service quality evaluation. Design/methodology/approach: Consistent with the critical realism paradigm a multi-method design is adopted for this study. Sociologist Pierre Bourdieu‟s (1986) structuralist perspective of culture is utilised as the analytical framework. Findings: The findings challenge both marketing and sociology theory that propose that individuals are less focussed on nurturing inter-personal relationships as they are empowered economically. Indeed it is found that social networks (i.e. social capital) perform a key role in service quality preference formation and dissemination. The evidence suggests that economic development has not mitigated the influence of social relationships upon service consumption. Research limitations/implications: Identifies a research agenda towards developing a measure of service quality that more comprehensively probes the social element of the service encounter. In order to more fully explore the impact of economic capital on the service quality construct it is identified that a longitudinal study is required that focuses upon nations as they transition from developing to developed nation status. Practical implications: This study has significant implications for marketing managers seeking to build a presence in Taiwan or other similarly profiled Confucian based societies. It is advised that strategists should adopt a customised strategic plan when operating within Taiwan and similarly profiled cultures. In particular this study encourages a focus upon nurturing inter-personal relationships and leveraging these relationships to effectively communicate to target markets in Confucian societies. Originality/value: This study adopts a sociological perspective of the cultural influence upon the service quality evaluation process.This approach is presented as preferable to the national values-oriented studies (e.g. Hofstede, 1984) that have dominated research in the area.